Pengembangan Potensi Desa Banjarwangi Kabupaten Garut Melalui Pelatihan Jurnalistik di Era Digitalisasi 4.0 - Adnan, Zulkifli; Adnan, Iis Zilfah; Fadhlurrohman, Mochammad Iqbal; Hendrawan, Mahardika Raihan; Munggaran, Panji (Universitas Garut, 2025)
The socialization and basic training activities in leadership and journalism at SMAN Nusa Bangsa, Banjarwangi Village, Garut Regency, aim to enhance students' knowledge and skills in leveraging the era of digitalization 4.0. This training includes the introduction of leadership theories, journalism basics, and the use of digital media such as professional cameras and smartphones. Starting with a socialization session on the importance of leadership and journalism, the material presented covers the definition of leadership, types of leadership, the role of leadership in organizations, and journalism techniques including news writing and interviewing. Practical training sessions are conducted through leadership simulations and hands-on practice in news writing and interviewing. Students are divided into small groups and assigned tasks to lead the group and create and present their journalistic work. The results of the activities show significant improvements in students' understanding and skills in leadership and journalism, and increase their motivation to pursue higher education. Students are also able to promote the potential of Banjarwangi Village, such as tourism, culinary arts, crafts, and agriculture through quality journalistic content. Evaluation and reflection demonstrate long-term positive impacts on village development and community welfare, making students active agents of change in utilizing digital technology to enhance local potential.